NARINGIN ATTENUATES OXIDATIVE STRESS AND PROTECT AGAINST MYOCARDIAL ISCHEMIA-REPERFUSION INJURY IN DIABETIC RAT - KUMARI, NEELAM; KUSHWAH, AJAY SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The relative risk of coronary heart disease in diabetic patients is more than in non-diabetic population. The present study was undertaken to explore the cardioprotective effect of Naringin on ischemia-reperfusion injury in the diabetic model of rat. Methods: Adult Wistar rats (either sex) divided into six groups. Diabetes was induced by 5 weeks combine exposure to a high-fat diet with a low dose of streptozotocin (30 mg/kg i.p.), administered on the 1st day of starting of the 5th week. Naringin treatment 25 mg/kg and 50 mg/kg was given simultaneously for 5 weeks. On the 36th day, the study animals were subjected to induction myocardial ischemia-reperfusion injury induced by the ligation of the left anterior descending coronary artery ligation in anesthetizing rat. Serum glucose level and cholesterol level measured before performing of ischemic reperfusion. After reperfusion injury, the animals were sacrificed and estimate change in the heart in the course of biochemical alterations, in creatine kinase-muscle/ brain (CK-MB) and lactate dehydrogenase, lipid peroxidation (LPO), glutathione (GSH), superoxide dismutase (SOD) and infarct size in the heart. Results and Conclusion: Naringin treatment significantly reduced the body weight, blood glucose, cholesterol, cardiac injury biomarkers, and LPO level and increased in antioxidant (GSH and SOD) level and also significantly increased in mean arterial pressure heart rate, reduced the myocardial infarction size. The present study concludes that Naringin 50 mg/kg being more prominent action to reduce the cardiotoxicity risk in ischemia-reperfusion injury state and increases myocardial susceptibility through having more prominent antioxidant potential properties.